PERAN TINGKAT LITERASI KEUANGAN SYARIAH DAN AKSES PEMBIAYAAN BANK SYARIAH TERHADAP PERTUMBUHAN USAHA MIKRO KECIL YANG DIMILIKI MUSLIM DI KABUPATEN BANDUNG - Nur'aeni Nur'aeni; Widyasari Widyasari (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2022)
Muslim entrepreneurs in Indonesia as a country with a Muslim majority have not yet reached the ideal proportion in their contribution to advancing the economy through the ownership of MSMEs. MSMEs owned by Muslims are still hampered in developing their businesses due to the level of Islamic financial literacy and insufficient access to Islamic banking. Thus, the purpose of this study is to examine the effect of Islamic financial literacy level and access to Islamic banking financing on the growth of MSMEs owned by Muslims. The study was conducted in Bandung Regency, which is the city/district with the most MSME ownership in the Greater Bandung area which includes Bandung City, Bandung Regency, Cimahi City, and West Bandung Regency. The research method used is a quantitative method with an explanatory approach. The stages of the research carried out were starting with preparing a research instrument in the form of a questionnaire as a tool to collect primary data from respondents. Then distributed questionnaires to respondents who are owners of Muslim SMEs in Bandung Regency. After the data has been collected, it is then recapitulated and analyzed using the Partial Least Square approach with the help of the WarpPLS application. The results showed that the level of Islamic financial literacy and access to Islamic bank financing did not significantly affect the growth of MSEs. Meanwhile, the level of Islamic financial literacy can affect the ease of access to Islamic bank financing for MSEs in Bandung Regency.